2020
DOI: 10.1088/1757-899x/970/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Concrete with Sintered Fly Ash Aggregate as Substitute of Natural Fine Aggregate

Abstract: Attempts have been made from time long to develop construction materials which should be strong, durable and simultaneously of light weight. In an attempt to reduce the self-weight of the structural concrete, light weight aggregates are being used and implemented. Fly ash is a waste material of coal based thermal power plants. Presently, fly ash is being used in construction industries in different ways. Sintered fly ash aggregates when used as a substitute for natural aggregates benefits the preservation of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The investigations associated with producing artificial lightweight aggregates and employing industrial wastes showed that the compressive and flexural strengths of the composite and its ductility could be improved. It was shown in Basa et al [3] study that using sintered fly ash aggregate as a replacement for fine aggregates enhanced compressive strength, splitting tensile strength, and flexural strength. Cold bonded fly ash lightweight aggregate was employed to increase the permeability of self-compacting concrete [4].…”
Section: Introductionmentioning
confidence: 99%
“…The investigations associated with producing artificial lightweight aggregates and employing industrial wastes showed that the compressive and flexural strengths of the composite and its ductility could be improved. It was shown in Basa et al [3] study that using sintered fly ash aggregate as a replacement for fine aggregates enhanced compressive strength, splitting tensile strength, and flexural strength. Cold bonded fly ash lightweight aggregate was employed to increase the permeability of self-compacting concrete [4].…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Sintered fly ash artificial aggregate as a replacement for fine aggregate improved the mechanical properties and fracture strength of concrete. [12] A compressive strength of concrete between 20 MPa and 80 MPa could be achieved using artificial aggregate. The axial strength of the concrete increased with the use of 10% of fly ash artificial aggregate as a replacement for natural coarse aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time ductility characteristics of artificial lightweight aggregates could be advanced. In the [1] study, it was found that the compressive, splitting, and the flexural strength values were improved using the sintered fly ash (FA) aggregate as a substituted material for the fine aggregates. Cold bonded pelletization manufacturing technique was utilized to produce ALAs [2].…”
Section: Introductionmentioning
confidence: 99%